Are facial, maxillary arch and incisor dimensions related in patients with a unilaterally impacted palatal canine? A prospective investigation - Koshak Lamis K.; Millett Declan T.; Kelly Niamh; McIntyre Grant T.; Cronin Michael S. (Sciendo, 2022)
To identify and determine the relationship between facial, maxillary arch and incisor dimensions of patients presenting with a unilaterally impacted palatal canine.